Efficacy of Black Cumin (Nigella sativa) Ameliorate Organophosphate Toxicity in Pregnant Rats Based on Progesterone Levels and Fetal Bone Development - Hendrawan, Viski Fitri; Agustina, Galuh Chandra; Aditya, Siska; Oktanella, Yudit; Firmawati, Aulia; Mariyam, Dewi (Universitas Airlangga, 2024)
Black cumin (Nigella sativa), also referred to as black cumin, is a versatile herbal treatment that has recently grown in popularity, it contains antimicrobial, antibacterial, antifungal, anti-inflammatory, analgesic, antipyretic, antiparasitic, antihistamine, antihypertensive, antitumor, anticancer, antidiabetic, and anti-asthmatic properties are just a few of the positive and pharmacological effects of active ingredients in black cumin, such as thymoquinone and other compounds. This study aimed to evaluate black cumin activity ameliorates organophosphate toxicity in pregnant rats based on progesterone levels and fetal bone development. In this study, pregnant albino rats were divided into five treatment groups i.e. (K-) placebo; (K+) treated an organophosphate; treated an organophosphate and black cumin extract at a dose of (P1) 200 mg/kg BW, (P2) 400 mg/kg BW, and (P3) 600 mg/kg BW. The progesterone levels serum and fetal bone development were evaluated and calculated using ANOVA followed by Turkey. The results showed that P2 and P3 groups significantly increase in progesterone levels compared to K+ and P1 groups. Fetal bone was also reported increase in the growth of caudal vertebrae. In conclusion, 400 mg/kg BW of black cumin could ameliorated progesterone levels and fetal bone development in pregnant rats with organophosphate toxicity.